Diversity of the southern Africa Lacustricola Myers, 1924 and redescription of Lacustricola johnstoni (Günther, 1894) and Lacustricola myaposae (Boulenger, 1908) (Cyprinodontiformes, Procatopodidae) - Pedro H. N. Bragança; Ryan M. van Zeeventer; Roger Bills; Denis Tweddle; Albert Chakona (ZooKeys, 2020)
Through the analysis of a comprehensive database of COI sequences, with the sequencing of 48 specimens, a first insight into the genetic diversity, distribution and relationships between the southern Africa “Lacustricola” species is presented. Species from “Lacustricola” occur mainly in freshwater systems within the arid savanna, and are considered to be widely distributed in southern Africa, but most of them are data deficient taxa. Two species are redescribed, “Lacustricola” johnstoni (Günther, 1894) and “Lacustricola” myaposae (Boulenger, 1908), based on specimens collected at their respective type localities. Detailed osteological and life colouration information is presented for the first time. “Lacustricola” johnstoni was described from the Upper Shire River in Mangochi, Lake Malawi but is herein considered as widespread in the Okavango, Zambezi, southern Africa east coastal drainages and the Bangweulu in the Congo System. A sympatric similar species occurring in the Okavango is also identified. “Lacustricola” myaposae (Boulenger, 1908), was described from the Nseleni River in KwaZulu-Natal Province, South Africa and is herein considered to be endemic to the small coastal river drainages within this region. Lectotypes for both “L.” johnstoni and “L.” myaposae are designated. A new species from the Lualaba River in the Congo System, sister to “L.” macrurus is identified, and the deep bodied “L.” jubbi is considered sister taxon to a clade including “L.” johnstoni and “L.” myaposae.